Retinal manifestations of patients with human immunodeficiency virus, a multiethnics study in Malaysia - Loo, A.V.P.; Sujaya, S.; Peyman, M.; Florence, S.; Subrayan, V (2011)
AIM: To investigate the fundus findings of patients infected with human immunodeficiency virus (HIV) in correlation to Highly Active Antiretroviral Therapy (HAART) and CD4 count. METHODS: Two hundred and two patients of the three major races (Chinese, Malay and Indian) in Malaysia were recruited in this population-based cross-sectional study. This consisted of confirmed HIV sero-positive patients with HAART treatment (n=95) or without HAART therapy (n=107) from December 2007 to March 2008. They were further classified into the HIV infected group, AIDS related complex (ARC) group and AIDS group. Each group was then subdivided according to their CD4 count. Clinical fundus findings were recorded. RESULTS: Sixty six patients (32.7%) showed presence of fundus manifestation, majority of which was HIV microangiopathy (89%) and the rest being Cytomegalovirus (CMV) retinitis (11%). The most common fundus lesion was cotton wool spot (34%). There was a higher incidence of fundus manifestation in the non HAART group than the HAART group (P=0.04) and in patients with CD4 count less than 200 cells/ml in both groups (P=0.01). The HAART therapy had remarkably reduced the percentage of fundus manifestation by 20% but CD4 count remains the marker for fundus manifestations. There were no significant differences noted in the retinal manifestation among the different races. (ANOVA, P=0.25). CONCLUSION: The fundus manifestations were higher in patients with CD4< 200 cells/ml and in the non HAART group. Hence the HAART therapy is capable of reducing the incidence of fundus manifestations, however the CD4 count determines the occurrence of fundus manifestations.